Increased risk of all-cause, Alzheimer’s, and vascular dementia in adults with migraine in Korea: a population-based cohort study - Kyungduk Hurh; Sung Hoon Jeong; Seung Hoon Kim; Suk-Yong Jang; Eun-Cheol Park; Sung-In Jang (The Journal of Headache and Pain, 2022)
Abstract Background Studies investigating the association between migraine and dementia have reported inconsistent findings. This study aimed to evaluate whether patients with migraine have an increased risk of dementia compared to individuals without migraine. Methods We obtained data from the 2002–2019 Korean National Health Insurance Health Screening Cohort. Non-migraine controls were selected using a 1:1 risk-set matching with a time-dependent propensity score. The main outcome was the development of all-cause dementia, and the secondary outcome was the development of each cause of dementia (Alzheimer’s, vascular, mixed or other specified, and unspecified dementia). The incidence rate of dementia was calculated using Poisson regression, and the association between migraine and dementia was evaluated using Cox proportional hazards regression. Results Among 88,390 participants, 66.1% were female, and the mean baseline age was 55.3 ± 9.4 years. During the study period, dementia cases were identified in 4,800 of the 44,195 patients with migraine and 3,757 of the 44,915 matched controls. The incidence rate of dementia was 139.6 (95% confidence interval [CI], 135.7–143.5) and 107.7 (95% CI, 104.3–111.1) cases per 10,000 person-years in patients with migraine and matched controls, respectively. Patients with migraine had a 1.30 (hazard ratio [HR], 1.30; 95% CI, 1.25–1.35), 1.29 (HR, 1.29; 95% CI, 1.23–1.35), 1.35 (HR, 1.35; 95% CI, 1.19–1.54), 1.36 (HR, 1.36; 95% CI, 1.00–1.83), and 1.30 (HR, 1.30; 95% CI, 1.17–1.45) times higher risk of developing all-cause dementia, Alzheimer’s dementia, vascular dementia, mixed or other specified dementias, and unspecified dementia than their matched controls, respectively. Conclusion Our results suggest that migraine is associated with an increased risk of subsequent dementia. Further research is warranted to confirm these findings and to reveal the underlying mechanisms.